Investigating the Effects of Al2O3 Microparticles on Wood Waste OSBs: A Study on Physical, Mechanical, and Durability Performance - Lopes, Wanley Eduardo; Cabral, Matheus Roberto; Christoforo, Andre Luis; Campos, Cristiane Inacio de [UNESP]; Fiorelli, Juliano (Mdpi, 2023)
The development of new materials for the construction sector is a global trend, and products that use by-products in their composition and have also incorporated technology are commercially competitive. Microparticles have large surface areas and can modify the microstructure of materials, positively affecting their physical and mechanical properties. In this context, this study aims to investigate the effect of incorporating aluminium oxide (Al2O3) microparticles on the physical and mechanical properties of oriented strand boards (OSBs) made from reforested residual balsa and castor oil polyurethane resin and to evaluate their durability performance under accelerated aging conditions. The OSBs were produced on a laboratory scale with a density of 650 kg/m(3), strand-type particles measuring 90 x 25 x 1 mm(3), using castor oil-based polyurethane resin (13%) and Al2O3 microparticle content ranging from 1% to 3% of the resin mass. The physical and mechanical properties of the OSBs were determined following the EN-300:2002 recommendations. The results obtained indicated that the OSBs with 2% Al2O3 presented thickness swelling significantly lower (at the 5% significance level) after being subjected to accelerated aging and internal bonding of the particles higher than the values obtained for the references, evidencing the positive effect of including Al2O3 microparticles in balsa OSBs.
Keywords: balsa wood; metal oxide; particleboards; polyurethane resin; wood